THE EFFECTIVENESS OF HEALTH EDUCATION BASED ON HEALTH BELIEF MODEL ON KNOWLEDGE PATIENT PULMONARY DISEASES (Al Insyirah International Scientific Conference on Health, 2021)
Tuberculosis is still the most dangerous infectious disease in the world.  Influincing Factors to increase of pulmonary tuberculosis disease are age, sex, nutrional status, diabetes mellitus, immunity status, smoking, alcohol and the enviroment. The purpose of this study was to determine the effectiveness of health education based on the Health Belief Model on knowledge patients of pulmonary disease.This type of research was a quasi experiment with one group design research design with pre-test and post test. The sample was 16 respondents with a total sampling technique. The results showed that there was a difference in knowledge of pre and post pulmonary tuberculosis patients who were given health education based on Health belief model (p value = 0,000). It is recommended to puskesmas to apply Health belief model in health education in order to improve the quality of community nursing care.
Keywords: Health Belief Model; Health Education; Knowledge; Pulmonary TB